Influence of construction deficiencies on the seismic response of structures. - Dimova, S.L (Earthquake engineering & structural dynamics.)
The quality of construction is one of the main factors that affect the seismic vulnerability of structures. The damage observations of modern buildings after almost all recent earthquakes report cases of poor quality of materials, inadequate detailing of reinforcement and absence of capacity design principles. Looking at the modern codes for seismic design, which rely on high behaviour factor supplies, the assessment of the effects of poor quality of execution in otherwise well-conceived and well-designed structures becomes an important problem. This paper presents an experiment based estimation of the seismic response of a cast-in-situ one storey industrial reinforced concrete frame designed according to Eurocodes. The influence of the quality of construction is estimated by consideration of two models of the experimental prototype : a structure erected under strict measures for control of the quality of execution, and a structure erected with normal measures for control of the quality of execution which resulted in significant deficiencies in the practical arrangement of the reinforcement. On the basis of the experimental data the ductility and behaviour factor supplies of the two structures are estimated. Quantitative expressions for the influence of the quality of construction on the first yield displacement, ultimate storey displacement, maximum base-shear force and behaviour factor supply are provided. Recommendations for the refinement of modern seismic design codes, particularly Eurocode 8, to take into account the quality of construction are given.